Effect of further grinding process on reduction of scale with carbonized almond shells - Boyrazli, Mustafa; Ozturk, Elif Aranci; Benkli, Yunus Emre; Sengul, Nadir; Saridede, Muhlis Nezihi; Yalcin, Mesut; Yakuphanoğlu, Fahrettin (Consejo Superior Investigaciones Cientificas-Csic, 2024)
Iron and steel manufacturing generates significant industrial waste, including mill scale, rich in valuable metal content. This study investigates the potential of mill scale recovery for metallic iron and the use of almond shells as an organic substitute for coke in reduction processes. Carbonization conditions for almond shells and advanced milling methods for both mill scale and carbonized almond shells are examined to enhance surface area and reactivity. Reduction experiments at varying temperatures unveil the metallization potential of mill scale. Notably, reduction at 1200 degrees C for 120 minutes achieves the highest metallic iron content of 94.6%. According to the results obtained, the use of carbonized almond shell significantly contributed to the reduction of mill scale material, and has thus been considered as an effective biomaterial in this context. These findings propose a sustainable solution for iron and steel production, offering an alternative and eco-friendly iron source for blast furnaces and electric arc furnaces.
Efecto del proceso de molienda adicional en la reducción de cascarilla con cáscaras de almendra carbonizadas
Keywords: Mill scale; Reduction; Carbonization; Almond shells; Mechanical activation; Iron nugget